2016
DOI: 10.1039/c6re00160b
|View full text |Cite
|
Sign up to set email alerts
|

Engineering chemistry: integrating batch and flow reactions on a single, automated reactor platform

Abstract: Synthesis chemistry need not be limited to either only batch or only flow; rather, in the future we expect that it will consist of an amalgamation of the best and most appropriate methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 23 publications
0
39
0
2
Order By: Relevance
“…[11] The system was further expanded by Fitzpatrick and Ley who used it to control continuous extraction in am ulti-step synthetic workflow. [12] Their design used an inexpensive web camera to detect the position of the green colored float and sent asignal to the Raspberry Pi SBC,which further sent commands to an Arduino MCB controlling asmall peristaltic pump.…”
mentioning
confidence: 99%
“…[11] The system was further expanded by Fitzpatrick and Ley who used it to control continuous extraction in am ulti-step synthetic workflow. [12] Their design used an inexpensive web camera to detect the position of the green colored float and sent asignal to the Raspberry Pi SBC,which further sent commands to an Arduino MCB controlling asmall peristaltic pump.…”
mentioning
confidence: 99%
“…[39] Flow synthesizers can also have limitations,such as clogging or insufficient mixing of suspensions. [40][41][42][43]…”
Section: Methodsmentioning
confidence: 99%
“…This work demonstrated that a combination of flow and batch conditions can be exceptionally effective to optimize time and yield. [40] Other groups have also recently emphasized the advantages of combining batch and continuous flow synthesizers. [4143] …”
Section: One Machine – One Small Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…In dieser Arbeit konnte gezeigt werden, dass die Kombination kontinuierlicher und diskontinuierlicher Bedingungen ein effektiver Weg zur Optimierung der Geschwindigkeit und Ausbeute sein kann. [40] Auch andere Gruppen konnten in letzter Zeit die Vorteile entsprechender kombinierter Synthesemaschinen zeigen. [41][42][43] Viele organische Verbindungen lassen sich so zumindest teilweise automatisch über angepasste Routen synthetisieren.…”
Section: Reproduzierbarkeitunclassified